PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA GURU DI SMK NEGERI 10 KECAMATAN SUNGAI GELAM KABUPATEN MUARO JAMBI - Lili Andriani, Mila Yumaroh (Universitas Batanghari Jambi, 2017)
This study aims to determine the picture of work environment and performance of teachers, and the influence of work environment on the performance of teachers at SMK Negeri 10 in Sungai Gelam District Muaro Jambi. The results showed that the work environment picture got a value of 75.26% enough categorized, while for the performance of teachers got a value of 75.00% categorized quite well. Meanwhile, for the influence of work environment on teacher performance result model summary R = 0,837 and R Square = 0,701. In ANOVA, the value of F = 77.487 with α (sig) = 0,000. Because α (Sig) <0.05, then regression can be used to predict the working environment at 95% confidence level. In coefficient the value of B constant = 14,062, states that if the work environment variable is ignored, then teacher performance = 14,062.Kata Kunci : Work Environment, Teacher Performance